Intervensi Tuhan dalam Keterlibatan Orang tua terhadap Gaya Belajar Generasi Pembelajar Mandiri (Homeschooling) - Chanita Christie (Sekolah Tinggi Teologia Kerusso Indonesia, 2022)
AbstractThe success of the child's growth and development process is an important task for parents inaccompanying and guiding children to reach the top of the destiny of every talent, passion andlonging to be realized. With world conditions that are not getting better, even if technology is gettingbetter and even starting to replace the roles and functions of humans in carrying out the process ofdaily activities. It really creates a lot of new problems, especially for the future generations of God'schurch in the future. Parents as the holder of an important role in the process of growth anddevelopment and formation of children's character are expected to become a dependent place forchildren in the world as representatives of God on earth. The author uses the literature studymethod to describe the form of God's intervention in parental involvement in the learning style of theSelf-Learning Generation (Homeschooling). Through literature studies by reading books, the authorcan formulate a useful view of God's intervention in parental involvement in the Learning Style ofthe Independent Learning Generation (Homeschooling)